Factors Attracting Foreign Direct Investment in the Lao PDR since 2006–2021 - THAMMAVONG, Phiengkham; SIPHANTHONG, Bounthavy; SIOUDOMPHAN, Soutthavone; SENGDARA, Chansamone (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Research on factors that attract foreign direct investment in Lao PDR from 2006–2021 This time, the collected data was compiled, interpreted, considered, selected, and analyzed statistically to find the percentage value and the parameter value of the regression equation using the least squares method (OLS) through the Microsoft Excel version 2022 program. The results of the research found that there are seven factors with statistical significance: gross domestic product (GDP), inflation rate (INF), foreign exchange rate (EXR), export value (EX), import value (IM), economic infrastructure (IFT), and labor force (L). As for the wage factor (W) and investment promotion policy (D), they are not statistically significant but can be used to create an economic model as follows: Lao PDR's gross domestic product (GDP) has a relationship in the same direction with foreign direct investment (FDI) with a statistical significance of 0.05. The inflation rate in Lao PDR (INF) has a relationship in the opposite direction with foreign direct investment (FDI), with statistical significance at 0.01. The foreign exchange rate (Kip/US Dollar) (EXR) has an inverse relationship with Foreign Direct Investment (FDI), with statistical significance at 0.05. Lao PDR's export value (EX) has a relationship in the same direction with foreign direct investment (FDI), with statistical significance at 0.01. The import value of goods from Lao PDR (IM) has a relationship in the opposite direction with foreign direct investment (FDI), with statistical significance at 0.05. For economic infrastructure (IFT), there is a relationship in the same direction as foreign direct investment (FDI), with statistical significance at 0.01. The labor force in Lao PDR (L) has a relationship in the opposite direction with foreign direct investment (FDI), with statistical significance at 0.05.